Create Video with Media Composer: Official Avid Curriculum - Avid Technology, Avid Technology (Rowman & Littlefield Publishers, 2023)
Create Video with Avid Media Composer introduces users to the power of Media Composer software and marks the first steps toward developing core skills in video editing. The book covers the basic principles you’ll need to complete a film project using Media Composer | First, from initial setup to final output, and it is designed for those who are new to professional video editing and also for experienced editors who are unfamiliar with Media Composer software. Each lesson and exercise will focus on a phase of the editing process, starting with organizing media, assembling a sequence, refining a sequence, creating titles and effects, and outputting your program so that others can view it. Although this book is not aimed at teaching the theory behind film and television production, the content provides some background on the craft of editing, making it appropriate for students and others new to the art. For those interested in gaining official Avid certification, this book is also a valuable introduction for further learning and through the Avid Learning Series curriculum.